Early Detection Of Covid-19 Infection By Examination Of Rapid Antibody Tests In Clusters Of Lecturers And Employees Of The University Of Muhammadiyah Malang - Thontowi Djauhari Nur Subchi; Zata Dini (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2022)
The Covid-19 pandemic that is currently hitting Indonesia requires the active role of all parties, including from institution Education. University Muhammadiyah Poor is the only private campus that has carried out general check-up activities with a covid-19 screening examination or rapid test for all lecturers and staff. The purpose of this activity is as a form of campus concern for the health of its lecturers and employees, especially during the current Covid-19 pandemic. In addition, the University of Muhammadiyah Malang held activities like this to support Government among them through activity devotion as part from implementation tridharma task of higher education. This research method uses an analytical survey method. Sampling using total sampling technique. The stages of implementing this activity began with registration carried out by UMM campus lecturers and employees, complete blood tests, and rapid tests and PCR swabs for those whose rapid results were reactive, and self-isolation if there was a lecturer or employee which results swab the PCR positive. Results from study this is could knowing the health status of lecturers and staff at the University of Muhammadiyah Malang. Of all employees who have registered as participant GCU this obtained 22 employee which results the swab positive or around 1.7% of the total number of employees who have undergone health screening (rapid test). This figure proves that the number of confirmed cases of Covid is still below 10%. As a follow-up, independent isolation is carried out for lecturers and employees who have tested positive for Covid-19 while remaining under supervision by campus staff and the Muhammadiyah University covid task force. Poor.